Evaluation of Green Silver Nanoparticles Fabricated by Spirulina platensis Phycocyanin as Anticancer and Antimicrobial Agents - Soror, Abel-Fattah Salah; Ahmed, Mai Waled; Hassan, Abdalla E. A.; Alharbi, Mona; Alsubhi, Nouf H.; Al-Quwaie, Diana A.; Alrefaei, Ghadeer I.; Binothman, Najat; Aljadani, Majidah; Qahl, Safa H.; Jaber, Fatima A.; Abdalla, Hanan (Life (Basel, Switzerland), 2022)
Green nanotechnology has attracted attention worldwide, especially in treating cancer and drug-resistant section 6 microbes. This work aims to investigate the anticancer activity of green silver nanoparticles synthesized by Spirulina platensis phycocyanin (SPAgNPs) on two cancer cell lines: Lung cancer cell line (A-549) and breast cancer cell line (MCF-7), compared to the normal human lung cell line (A138). We also aimed to investigate the bactericidal activity against Staphylococcus aureus ATCC29737, Bacillus cereus ATCC11778, Escherichia coli ATCC8379, and Klebsiella pneumonia, as well as the fungicidal activity against Candida albicans (ATCC6019) and Aspergillus niger. The obtained SPAgNPs were spherical and crystalline with a size of 30 nm and a net charge of −26.32 mV. Furthermore, they were surrounded by active groups responsible for stability. The SPAgNPs scavenged 85% of the DPPH radical with a relative increase of approximately 30% over the extract. The proliferation of cancer cells using the MTT assay clarified that both cancer cells (A-549 and MCF-7) are regularly inhibited as they grow on different concentrations of SPAgNPs. The maximum inhibitory effect of SPAgNPs (50 ppm) reached 90.99 and 89.51% against A-549 and MCF7, respectively. Regarding antimicrobial activity, no inhibition zones occurred in bacterial or fungal strains at low concentrations of SPAgNPs and the aqueous Spirulina platensis extract. However, at high concentrations, inhibition zones, especially SPAgNPs, were more potent for all tested microorganisms than their positive controls, with particular reference to Staphylococcus aureus, since the inhibition zones were 3.2, 3.8, and 4.3 mm, and Bacillus cereus was 2.37 mm when compared to tetracycline (2.33 mm). SPAgNPs have more potent antifungal activity, especially against Aspergillus niger, compared to their positive controls. We concluded that SPAgNPs are powerful agents against oxidative stress and microbial infection.